2005
DOI: 10.1093/qjmed/hci139
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on multiple medications versus combined pills: a qualitative study

Abstract: While some patients would be willing to try a combined pill and would appreciate the associated convenience, they are likely to have a number of concerns that prescribers should address. Willingness to move to combined therapy may be hindered if drug combinations that mirror personalized and trusted regimens are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Multiple diseases and complex medicine regimes in elderly patients may compromise adherence even further [3,4]. Studies of regimen simplification, like reduced dose frequency, often focus on patient adherence only and fail to include measures of satisfaction or acceptability by patients or show that simplification leads to clinical improvements [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple diseases and complex medicine regimes in elderly patients may compromise adherence even further [3,4]. Studies of regimen simplification, like reduced dose frequency, often focus on patient adherence only and fail to include measures of satisfaction or acceptability by patients or show that simplification leads to clinical improvements [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains many studies on patients' experiences of medicine-taking in general, among different patient groups [10], but few focus on elderly and/or users of multiple medicines [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been found to be a concern from patients about combined pills in general. 10 Therefore the move to a polypill for secondary prevention may be problematic if the new drug regimen does not mirror the old trusted one.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…9 In terms of patients' attitudes towards combined pills in general, most see little clinical benefit in changing from an established, effective, and tolerable regimen to one that is less flexible and may not reflect their current dosages, although some would be willing to try a combined pill if suggested by their doctor. 10 When it comes to statins, studies have shown patients have concerns regarding unwanted side effects, with many preferring to make lifestyle changes instead. 11,12 Similar attitudes are held towards antihypertensives, [13][14][15] although many patients will take them because of positive experiences with doctors, perceived benefits, and pragmatic reasons.…”
Section: Introductionmentioning
confidence: 99%